Pengaruh Pencahayaan pada Showroom Terhadap Kenyamanan Visual (Studi Kasus Showroom Harley Davidson, Bandung) - Kurniawan, Rudy; Santoso, Miky Endro; Darmayanti, Tessa Eka (Program Studi Desain Interior Unikom, 2022)
The role of lighting is an important part of a space design. Its function is not just to be a light, but can create and offer a certain atmosphere that can support its function, in this case the Harley-Davidson Motorcycle showroom. A pleasant atmosphere and providing comfort can make a display object more attractive so as to create a separate experience for consumers or anyone who comes to the showroom. The role of lighting can make a difference in the Harley-Davidson showroom in Bandung with other showrooms. The purpose of this study is to find out the right lighting in the Harley Davidson showroom in Bandung. The research method used is a descriptive approach in the form of written or spoken words from observable people and actors.. based on the showroom that author studied, it was found that the intensity, color and type of lighting are the components of visual comfort and create the image, identity and attractiveness of a showroom. Indirectly, this shows that lighting does not only have tangible values that can be seen by the eye, but also has intangible values that can be felt by the five human senses, one of which is a sense of comfort.